Sex Difference Trend in 5-Year Mortality Among Patients With Coronary Artery Disease: A 24,432 Chinese Cohort Study From 2007 to 2014 - Huang, Haozhang; Lai, Wenguang; Li, Qiang; Wei, Haiyan; Remutula, Nuerbahaer; Tuersun, Tilakezi; Yang, Zhou; Bao, Kunming; Yan, Zelin; Wang, Bo; He, Yibo; Chen, Shiqun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: The sex differences trend of short-term mortality in coronary artery disease (CAD) is narrowing, which has been reported in previous studies. However, no studies assess that sex different temporal trends of CAD mortality in China especially long-term mortality trend. Methods Based on the registry at Guangdong Provincial People's Hospital which is the largest cardiovascular center in South China, this retrospective cohort study included 24,432 hospitalized CAD patients confirmed by coronary angiography from January 2007 to December 2014. Female and male were followed for 1-year and 5-year all-cause mortality. Results From 2007 to 2014, 5-year age-standardized mortality increased from 10.0% to 11.7% in male (P for trend <0.001) and from 11.5% to 8.1% in female (P for trend = 0.99). The multivariable-adjusted hazard ratios (95% CI), comparing female with male were from 1.02 (0.39-2.67) to 0.66 (0.39-1.12) for 1-year all-cause mortality, 1.23 (0.64-2.36) to 0.59 (0.44-0.79) for 5-year all-cause mortality (P for trend = 0.04). Conclusion Our study found that the mortality risk among men and women was similar in the 1-year prognosis of CAD, and there was no significant downward trend. In the 5-year long-term prognosis of CAD, the mortality risk among male continued to rise, while female had reached the peak, which means that the mortality risk continues to be higher among male than female.